Rural progress through co-operatives : the place of cooperative associations in agricultural development (New York : United Nations, 1954)
This book is set out to systematically analyse variety that must be done to effectively accomplished a progress in farming especially in the rural life.
"United Nations publication. Sales no. : 1954. II. B. 2."
Includes bibliographical references.
asm 24/01/2019
Loans
Keywords: Agriculture, Cooperative